Lumbopelvic Control and the Development of Upper Extremity Injury in Professional Baseball Pitchers. Issue 4 (March 2021) - Laudner, Kevin; Wong, Regan; Evans, Daniel; Meister, Keith
Background: The baseball-throwing motion requires a sequential order of motions and forces initiating in the lower limbs and transferring through the trunk and ultimately to the upper extremity. Any disruption in this sequence can increase the forces placed on subsequent segments. No research has examined if baseball pitchers with less lumbopelvic control are more likely to develop upper extremity injury than pitchers with more control. Purpose: To determine if baseball pitchers who sustain a chronic upper extremity injury have less lumbopelvic control before their injury compared with a group of pitchers who do not sustain an injury. Study Design: Cohort study; Level of evidence, 2. Methods: A total of 49 asymptomatic, professional baseball pitchers from a single Major League Baseball organization participated. Lumbopelvic control was measured using an iPod-based digital level secured to a Velcro belt around each player's waist to measure anteroposterior (AP) and mediolateral (ML) deviations (degrees) during single-leg balance with movement and static bridge maneuvers. During a competitive season, 22 of these pitchers developed upper extremity injuries, while the remaining 27 sustained no injuries. Separate 2-tailed t -tests were run to determine if there were significant differences in lumbopelvic control between groups ( P < .05). Results: There were no significant between-group differences for the stride leg (nondominant) during the bridge test in either the AP ( P = .79) or the ML ( P = .42) directions, or either direction during the drive leg bridge test ( P > .68). However, the injured group had significantly less lumbopelvic control than the noninjured group during stride leg balance in both the AP ( P = .03) and the ML ( P = .001) directions and for drive leg balance in both the AP ( P = .01) and the ML ( P = .04) directions. Conclusion: These results demonstrate that baseball pitchers with diminished lumbopelvic control, particularly during stride leg and drive leg single-leg balance with movement, had more upper extremity injuries than those with more control. Clinicians should consider evaluating lumbopelvic control in injury prevention protocols and provide appropriate exercises for restoring lumbopelvic control before returning athletes to competition after injury. Specific attention should be given to testing and exercises that mimic a single-limb balance task.